2013
DOI: 10.1590/s0100-736x2013001000003
|View full text |Cite
|
Sign up to set email alerts
|

Doenças do sistema nervoso de bovinos no Mato Grosso do Sul: 1082 casos

Abstract: Foi realizado um estudo retrospectivo de janeiro de 2008 a dezembro de 2012 com base nos laudos de necropsia do Laboratório de Anatomia Patológica (LAP) da Faculdade de Medicina Veterinária e Zootecnia (FAMEZ), Universidade Federal de Mato Grosso do Sul (UFMS), com o intuito de descrever quais as doenças que afetam o sistema nervoso de bovinos que ocorrem no Mato Grosso do Sul. Os casos consistiam de acompanhados por técnicos do LAP e encaminhados por médicos veterinários que atuam no campo (autônomos ou do se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
18
0
21

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 46 publications
10
18
0
21
Order By: Relevance
“…Excluding this case, the morbidity ranged from 8.1 to 30.7%, which is a range close to that reported in the other outbreaks. The case-fatality rates described in the literature ranged from 48.5-100% (NAKAZATO et al, 2000), 50-100% (SANT 'ANA et al, 2009a;RIBAS et al, 2013), and 66.6-100% (LIMA et al, 2005), is similar to those obtained herein. Results of CSF analysis showed a density above the physiological parameters or in the upper limit for four cases.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Excluding this case, the morbidity ranged from 8.1 to 30.7%, which is a range close to that reported in the other outbreaks. The case-fatality rates described in the literature ranged from 48.5-100% (NAKAZATO et al, 2000), 50-100% (SANT 'ANA et al, 2009a;RIBAS et al, 2013), and 66.6-100% (LIMA et al, 2005), is similar to those obtained herein. Results of CSF analysis showed a density above the physiological parameters or in the upper limit for four cases.…”
Section: Discussionsupporting
confidence: 87%
“…In other studies, considering the total population for calculation, the authors indicate the morbidity of 0.02-14.28% (NAKAZATO et al, 2000); 0.04-6.66% (SANT'ANA et al, 2009a);12-20% (LIMA et al, 2005); and 8.34-38.76% (RIBAS et al, 2013). Highest morbidity in the present study was observed in Isolated Case 1, which belonged to a herd of only two sheep.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Considerando-se a população sob risco os 5.000 bovinos vacinados, esses dados corresponderiam a um coeficiente de morbidade de 0,36%. Embora aparentemente baixo este coeficiente é semelhante ao encontrado na maioria dos surtos por doenças responsáveis por importantes perdas econômicas em bovinos no MS, como a raiva e o botulismo (Ribas et al 2013). Levando em conta o valor pago ao produtor pelo quilo do boi abatido, que em setembro de 2012 era de R$ 6,13 (CEPEA/ ESALQ 2012), a perda total correspondeu a R$ 20.412,90.…”
Section: Discussão E Conclusõesunclassified
“…Vampire bats, specifically, Desmodus rotundus, are the main reservoirs of the virus in Latin America and are principal transmitters of rabies to herbivores (SCHNEIDER et al, 2009). Ribas (2013) and Lima et al (2005) reported higher incidence of rabies in cattle in Mato Grosso do Sul and Paraíba, principally occurring in animals under the age of 4 months, which may be related to the lower immunity of young animals, even if they have been previously vaccinated. According to some authors, the use of only one dose of vaccine is insufficient to protect the animals against rabies, with booster doses being required for the vaccination to offer effective protection (ALBAS et al, 2005).…”
Section: Introductionmentioning
confidence: 97%